GeneLynx: A Gene-Centric Portal to the Human Genome - Lenhard, Boris (Cold Spring Harbor Laboratory Press, 2001)
GeneLynx is a meta-database providing an extensive collection of hyperlinks to human gene-specific information in diverse databases available on the Internet. The GeneLynx project is based on the simple notion that given any gene-specific identifier (accession number, gene name, text, or sequence), scientists should be able to access a single location that provides a set of links to all the publicly available information pertinent to the specified human gene. GeneLynx was implemented as an extensible relational database with an intuitive and user-friendly Web interface. The data are automatically extracted from more than 40 external resources, using appropriate approaches to maximize coverage of the available data. Construction and curation of the system is mediated by a custom set of software tools. An indexing utility is provided to facilitate the establishment of hyperlinks in external databases. A unique feature of the GeneLynx system is a communal curation system for user-aided annotation. GeneLynx can be accessed freely at http://www.genelynx.org.